2018
DOI: 10.1016/j.bpj.2017.11.2767
|View full text |Cite
|
Sign up to set email alerts
|

NuMA Recruits Dynein Activity to Microtubule Minus-Ends at Mitosis

Abstract: To build the spindle at mitosis, motors exert spatially regulated forces on microtubules. We know that dynein pulls on mammalian spindle microtubule minus-ends, and this localized activity at ends is predicted to allow dynein to cluster microtubules into poles. How dynein becomes enriched at minus-ends is not known. Here, we use quantitative imaging and laser ablation to show that NuMA targets dynactin to minus-ends, localizing dynein activity there. NuMA is recruited to new minus-ends independently of dynein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…In addition, we confirmed that, in the absence of NuMA, p150 Glued was strongly displaced from the acentrosomal spindle poles (Appendix Fig S7H). Thus, it is likely that NuMA is essential for the recruitment of p150 Glued at the acentrosomal spindle pole, as was observed at centrosomal pole (Hueschen et al, 2017; Appendix Fig S7G). Collectively, these results suggest that NuMA is important for placing the monopolar spindle in the center of acentrosomal cells, in prior to formation of bipolar spindles.…”
Section: Numa Plays a Critical Role In Promoting Mitotic Spindle Bipomentioning
confidence: 77%
See 4 more Smart Citations
“…In addition, we confirmed that, in the absence of NuMA, p150 Glued was strongly displaced from the acentrosomal spindle poles (Appendix Fig S7H). Thus, it is likely that NuMA is essential for the recruitment of p150 Glued at the acentrosomal spindle pole, as was observed at centrosomal pole (Hueschen et al, 2017; Appendix Fig S7G). Collectively, these results suggest that NuMA is important for placing the monopolar spindle in the center of acentrosomal cells, in prior to formation of bipolar spindles.…”
Section: Numa Plays a Critical Role In Promoting Mitotic Spindle Bipomentioning
confidence: 77%
“…We next addressed the mechanisms underlying NuMA assembly for acentrosomal spindle pole formation. It has been established that NuMA is transported toward the spindle poles in a microtubule‐based motor dynein‐dependent manner (Merdes et al , , ; Hueschen et al , ). Therefore, we validated the requirement of microtubules and dynein for NuMA assembly at acentrosomal spindle poles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations